METALLIFEROUS MINING GEOPHYSICS-STATE OF THE ART IN THE LAST DECADE OF THE 20TH CENTURY AND THE BEGINNING OF THE NEW MILLENNIUM - Nabighian M.N.; Asten M.W. (My University, 2002)
The downturn in mining activity experienced during the 1990s did not preclude significant new developments in various areas of mining geophysics. The methodology for acquiring and compiling data has kept pace with the latest technological developments, from Global Positioning System navigation to raster displays and parallel computing. Wavelet transforms, principal component analysis, and fractals have begun to find successful applications in both processing and interpretation of geophysical data. Methods of quantitatively interpreting/inverting anomalies in terms of 2‐D and 3‐D models of causative bodies are becoming common. For the first time it is possible to make airborne gravity gradient measurements suitable for use in mineral exploration. Lower transmitter frequencies for airborne time‐domain electromagnetic (EM) systems have enabled surveys in areas where conductive cover previously screened basement conductors. The use of approximation algorithms has allowed the transformation of either time‐domain or frequency‐domain data into conductivity‐depth images (CDIs) which expedite interpretation. Full‐waveform recording and the use of multiple receivers are becoming common for ground EM techniques. In radiometrics it is now common practice to record 256 channels of spectral data which, by using statistical methods, has led to a dramatic reduction of noise in aerial gamma‐ray surveys. Finally, advances in 3‐D oil‐field seismic reflection methods have been introduced into the search for mineral deposits, thereby providing new tools for studying the environment of orebody emplacement as well as detailed geometrical information of value for both exploration and mine‐planning applications. Thus, at the beginning of the 21st century, we find the geophysical techniques used by the mining industry to be at the forefront of the latest technological developments.